(untitled) (Zona Laut Jurnal Inovasi Sains Dan Teknologi Kelautan, 2022)
OT ship. Skylie is a type of tanker produced by PT. Samudra Marine Indonesia, in its construction, applies a keel cooler as a cooling device for the main engine propulsion of ships. This keel cooler is one of the new types of heat exchangers which is applied in the field of shipping. A cooling system using a keel cooler is a closed-circuit cooling system that is installed externally on the hull below the waterline. This study aims to determine the overall heat transfer value and the effect of changes in ship power/torque on the effectiveness of the keel cooler-type heat exchanger. The analysis uses two methods, namely CFD analysis and simulation using the Ansys CFX R20 application. Based on the results of calculations on several ship power/torque conditions, the largest heat transfer value is obtained namely 5.599 x 10 5 W at 100% power condition and the lowest value is 5.055 x 105 W at 10% power condition. Meanwhile, the highest effectiveness value is 79.985% and the smallest value is 79.839%. So it can it was concluded that the use of the keel cooler on the OT ship. Skylie has met the standard value of effectiveness for a heat exchanger that is equal to 50%.